Pengaruh Literasi Keuangan Dan Financial Technology Terhadap Inklusi Keuangan Pada Mahasiswa Angkatan 2019 Fakultas Ekonomi Dan Bisnis Universitas Buana Perjuangan Karawang - Windi Putri; Wanta Wanta; Asep Darojatul Romli (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to determine the partial and simultaneous effect of financial literacy and financial technology on the financial inclusion of class 2019 students at the Faculty of Economics and Business, Buana Perjuangan University, Karawang. The method used in this study is a quantitative method. This research was conducted on class 2019 students from the Faculty of Economics and Business, Buana Perjuangan University, Karawang. The sample of this research is 86 respondents with the sampling technique using the slovin formula. The analytical model used in this study is path analysis with partial and simultaneous hypothesis testing. The results of this study indicate that financial literacy and financial technology show a positive correlation and there is a significant positive effect between each of the independent variables on the dependent variable. and there is a simultaneous influence on financial inclusion in class 2019 students of the Faculty of Economics and Business, Buana Perjuangan University, Karawang. Keywords : financial literacy, financial technology, financial inclusion